1988
DOI: 10.1139/f88-080
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Low-Level Gas Supersaturation on Lake Trout (Salvelinus namaycush)

Abstract: Eggs, eleutheroembryos, and alevins of lake trout (Salvelinus namaycush) were reared in 1 of 10 levels of total gas pressure (TCP) ranging from 13 to 81 mm Hg (ΔP) above ambient barometric pressure. Rearing water was soft (30–40 mg CaCO3/L, pH 6.8), temperature was 9.3 °C, and the exogenous feeding portion of the test lasted 98 d. The supersaturation levels tested had no effect on the total survival of eggs, eleutheroembryos, or alevins, and condition factor and mean weight of fish in each treatment were stati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
2

Year Published

1989
1989
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 9 publications
2
15
2
Order By: Relevance
“…This included eye haemorrhages after 36-day exposures (Table 2), a phenomenon which did not occur in higher AP levels that had higher O2 partial pressures. Krise & Meade (1988) found no visible signs of GBT in lake trout at AP as high as 81 mm Hg where N. + Ar levels did not reach 110% until AP 61. Partial pressures of N2 were higher in this sac fry study and oxygen levels were 7 3% lower (overall mean 99 5 vs 92 2) over the AP range of 42-96.…”
Section: Discussionmentioning
confidence: 78%
“…This included eye haemorrhages after 36-day exposures (Table 2), a phenomenon which did not occur in higher AP levels that had higher O2 partial pressures. Krise & Meade (1988) found no visible signs of GBT in lake trout at AP as high as 81 mm Hg where N. + Ar levels did not reach 110% until AP 61. Partial pressures of N2 were higher in this sac fry study and oxygen levels were 7 3% lower (overall mean 99 5 vs 92 2) over the AP range of 42-96.…”
Section: Discussionmentioning
confidence: 78%
“…Mortality increased at high gas pressures (AP 108 and 159), but mean growth did not decrease with higher supersaturation, except when feeding was reduced to about 50% of 3 the normal rate (Krise et al 1990). Long-term studies indicated no difference in growth rate of lake trout reared in 10 levels of supersaturation ranging from AP 13 to 81 (Krise and Meade 1988). Dawley and Ebel (1975) reported a marked increase in mortality and reduction of growth in fingerling chinook salmon and steel head held at gas levels of 105, 110, and 115% dissolved nitrogen and about 101, 106, and 111% total gas saturation (estimated AP to 80).…”
Section: Resultsmentioning
confidence: 99%
“…Lake trout (Lake Superior strain) were initially stocked in groups of 100 fish into 40.6-L glass rearing tanks (Krise and Meade 1988) and held TABLE 1.-Mean percent gas supersaturation associated with differential gas pressures (AP) in lake trout tests: total gas pressure (TCP), dissolved oxygen (DO), dissolved nitrogen + argon (DM), and ratio of oxygen to nitrogen (O2:N 2 ). Standard deviation (SD) is shown for for 1 year.…”
Section: Methodsmentioning
confidence: 99%
“…Few obvious signs signal the effects of sublethal gas Supersaturation except at gas pressures that provoke external emphysemas on the fish. Petechial hemorrhaging may occur in some fish (Stroud and Nebeker 1976;Krise and Meade 1988), but hemorrhages may also be absent, or if present, they could indicate a pathogenic infection.…”
mentioning
confidence: 99%